1982
DOI: 10.3758/bf03197627
|View full text |Cite
|
Sign up to set email alerts
|

The role of familiarity in determining typicality

Abstract: Ashcraft (l978b) found that people tend to know more properties of instances they rate as typical of a category than of instances they rate as atypical. This suggests that variations in typicality result from variations in familiarity. Three experiments are presented that challenge or qualify this suggestion. Experiment 1 showed that subjects sometimes produce more properties for items they rate as low in typicality. Experiment 2 showed that in a large, random sample of items, there was a tendency to produce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
5

Year Published

1988
1988
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 12 publications
5
70
0
5
Order By: Relevance
“…By including mean rated familiarity for each item in the analysis, McCloskey's suggestion can be rigorously tested in the case of the categorization times measured here. (Other effects of familiarity were reported by Glass & Meany, 1978, Larochelle & Pineau, 1994, and Malt & Smith, 1982 Finally, regression analysis was also applied to the correct response rates (or more specifically to the probability of a positive category decisionj' for individual instances in the 12 categories. Negative responses resulting from a failure to retrieve an "is a" link may be expected to be associated with low PF, whereas those owing to low featural similarity should be associated with low typicality.…”
Section: Methodsmentioning
confidence: 99%
“…By including mean rated familiarity for each item in the analysis, McCloskey's suggestion can be rigorously tested in the case of the categorization times measured here. (Other effects of familiarity were reported by Glass & Meany, 1978, Larochelle & Pineau, 1994, and Malt & Smith, 1982 Finally, regression analysis was also applied to the correct response rates (or more specifically to the probability of a positive category decisionj' for individual instances in the 12 categories. Negative responses resulting from a failure to retrieve an "is a" link may be expected to be associated with low PF, whereas those owing to low featural similarity should be associated with low typicality.…”
Section: Methodsmentioning
confidence: 99%
“…This indicates that much of the apparent explanatory power of the label and token frequency measures in the overall analysis stems from the contrast between birds that the individuals encounter either in books or in the environment and those that they do not; the former are judged as more typical than the latter. This is the response bias referred to above (Malt & Smith, 1982). Among birds encountered both in the natural world and in the written word, variation in the number of instances of the birds has no effect on typicality judgments.…”
Section: Discussionmentioning
confidence: 99%
“…They found that unfamiliar atypical items have faster RTs than familiar atypical items, indicating that familiarity is not the only determinant of RT. Malt and Smith (1982) showed that part ofthe reason for Ashcraft's (1978) result was a response bias to assign low typicality ratings to unfamiliar words. They, like Hampton and Gardiner (1983), concluded that familiarity is not the crucial variable in determining typicality.…”
Section: Familiaritymentioning
confidence: 99%
“…Familiarity is known to play a role in how people rate typicality (Barsalou, 1985;Hampton and Gardiner, 1983;Malt and Smith, 1982;McCloskey, 1980). When items are unfamiliar they are normally given lower typicality ratings.…”
Section: Accounting For Residual Variancementioning
confidence: 99%